PENDIDIKAN AGAMA ISLAM DI KELUARGA HOME INDUSTRI KONVEKSI DESA WONOREJO POLOKARTO SUKOHARJO TAHUN 2021 - Wildhan Zulfikar; Fauzi Muharom (STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
Educating is giving a good habit and continuously for humans from birth to adulthood. Therefore, our religion Islam specializes in education itself as the foundation of every Muslim and Muslim woman and applies throughout her life continuously. Types and Approaches This research is a field research using a qualitative approach. Collecting data and information objectively to produce valid, current and relevant information from the focus of research related to Islamic Religious Education in the family home industry convection village of Wonorejo Polokarto Sukoharjo. Analysis through data reduction, data presentation and conclusion drawing. The results of the study that Islamic Religious Education in the Family is a direction, habituation, and evaluation in carrying out orders to Allah SWT and avoiding all prohibitions. Some of the methods and paths of education carried out by parents include the habit of praying in this case the parents also try to provide a good example/uswah for their children, then the habituation of parents in terms of providing good religious learning with regular studies held every day by the family, and also practice discipline in all activities in this case each family has its own way of practicing it for their respective children. From the brief description above, we understand that every family has similarities and differences in educating their children, but still with one goal, namely to prepare a better generation for the future.